Culture, Identity and Resistance: Elements for a Debate About the Role of Cultural Management in the Construction of Community Identity (Palimpsesto, 2021)
This paper aims to reflect about cultural management as a tool to resist the hegemonic dynamics of capitalism, and the role of the community-engaged art as instrument for creating community identity.At first, the concepts of hegemony and symbolic violence and their relationship with culture are analysed; then, the challenges and contradictions in the enlargement of artistic repertoires are discussed; finally, this paper focuses on the community construction of the symbolic, to think the political character of cultural management.
Keywords: Cultural management; hegemony; symbolic violence; resistance; community art